Albertsen, K., Mac, A., Thoft, E., Limborg, H. J., Hansen, A. M. (2022). Professionel kapital i folkeskolen – faglighed og samarbejde i fokus - Olesen, Kristian Gylling (Tidsskrift for Arbejdsliv, 2022)